Description Of Adolescent Self-Concept with Authoritarian Parenting - Jalal, Novitamaulidya; Nur Nilam Sari (International Journal of Education, Vocational and Social Science, 2023)
This study aims to find out how the self-concept picture of adolescents who have parents with authoritarian parenting styles. The focus of this research is the subject's meaning of the authoritarian parenting style of their parents and the impact of the authoritarian parenting style on the self-concept picture. The research method used is a qualitative method with a phenomenological approach. The subjects in this study were 17-year-old women who had authoritarian parents. Data collection was taken using semi-structured interviews, observation and documentation. The results of this study indicate that the research subjects interpret parenting with feelings of depression but still live it even though they know the impact on their lives and the subjects have a positive self-concept.